Analysis of the Effect of Leverage Ratios, Profitability Ratios, and Company Size on Profit Growth - Nika Purniawati; Ismunawan (ORGANIZE: Journal of Economics, Management and Finance, 2023)
The research aims to tested whether profit growth in beverage and food sub-sector manufacturing companies listed on the IDX is influenced by leverage ratios, profitability ratios and company size. The population based on this research is the food and beverage sub-sector companies listed on the IDX 2018-2021. This research uses multiple linear regression analysis as a method of analysis of preliminary data and a sample of 5 companies. From the results, profit growth in manufacturing companies in the beverage and food sub-sectors listed on the IDX is positively influenced by the DER, ROA and company size